2019
DOI: 10.1016/j.radcr.2019.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Undifferentiated carcinoma of the pancreas with osteoclast-like giant cells showing intraductal growth and intratumoral hemorrhage: MRI features

Abstract: We report a case of undifferentiated carcinoma of the pancreas with osteoclast-like giant cells ocalized within the main pancreatic duct (MPD). A 61-year-old woman was referred to our hospital for evaluation of dilatation of the MPD that was detected on screening sonogram. Preoperative MR imaging revealed a small hypervascular tumor within the dilated MPD, showing high signal on R2* map and signal reduction on in-phase as compared to out-of-phase. R2* hyperintensity and in-phase signal reduction may be a chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Tumor obstruction of the biliary tract may 15,[19][20][21] which occurred in one of our cases. Tumor compression of the pancreatic duct may cause pancreatitis 22 or dilation of the pancreatic duct, 23 and there may be complaints of discomfort due to elevated tumor markers 24 or incidental detection of other diseases during examination. 25,26 The preoperative diagnosis of UCOGCP mainly depends on CT and MRI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tumor obstruction of the biliary tract may 15,[19][20][21] which occurred in one of our cases. Tumor compression of the pancreatic duct may cause pancreatitis 22 or dilation of the pancreatic duct, 23 and there may be complaints of discomfort due to elevated tumor markers 24 or incidental detection of other diseases during examination. 25,26 The preoperative diagnosis of UCOGCP mainly depends on CT and MRI.…”
Section: Discussionmentioning
confidence: 99%
“…PETCT can provide useful information about the metabolic status of the tumor and the presence or absence of distant metastasis. 23,27,28 ERCP also plays a role in the diagnosis of UCOGCP involving the papilla of duodenum and pancreatic bile duct. Enhanced CT could be used to differentiate UCOGCP from other tumors, such as PDAC or SPT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The early body of literature regarding these tumors, comprised exclusively of case reports, suggests that they carry a poor prognosis that is even worse than that of undifferentiated pancreatic adenocarcinoma, largely because of late presentation and frequent recurrence after resection 1 . Limited available estimates from these case reports suggest an overall survival (OS) of less than 1 year from time of diagnosis 1,2,4,6,8–11 . However, a more recent study has suggested that OGC of the pancreas may in fact carry a better prognosis that some other subtypes of undifferentiated carcinoma of the pancreas, specifically pleomorphic cell carcinoma.…”
mentioning
confidence: 99%
“…1 Limited available estimates from these case reports suggest an overall survival (OS) of less than 1 year from time of diagnosis. 1,2,4,6,[8][9][10][11] However, a more recent study has suggested that OGC of the pancreas may in fact carry a better prognosis that some other subtypes of undifferentiated carcinoma of the pancreas, specifically pleomorphic cell carcinoma. The authors also suggest that there is heterogeneity in disease burden at presentation and outcomes within different subtypes of undifferentiated pancreatic carcinoma.…”
mentioning
confidence: 99%